VD_FINDINFO HC / 2019 / 554 vom 20. Juni 2019 - VD Tribunal cantonal (2019)
MESURE PROVISIONNELLE, COPROPRIÉTÉ, ASSEMBLÉE GÉNÉRALE, LÉGITIMATION ACTIVE ET PASSIVE | 647 CC, 261 al. 1 CPC (CH), 316 al. 3 CPC (CH)